Resilience and relapse risk in Emirate adult patients with substance use disorder: a national cross-sectional study from the United Arab Emirates - Mhaidat, Ibraheem; Al-Yateem, Nabeel; Al-Mamari, Samya; Al-Suwaidi, Fatima (Frontiers in Psychiatry, 2024)
The United Arab Emirates is among the countries affected by substance use disorders (SUDs), which have economic and social impacts. Relapse after successful rehabilitation is a major issue in the treatment of SUD. Several factors increase the risk of relapse in patients with SUD, such as craving and negative social experiences. Resilience could empower patients struggling with SUD. This study aims to explore levels of resilience and relapse risk in adult Emirati patients diagnosed with SUD, and also the possible correlation between the two variables. Methods: Two hundred eighty-six Emirati adult patients with SUD completed a selfadministered questionnaire for demographics, resilience (Connor and Davidson Resilience Scale), and relapse risk (Stimulant Relapse Risk Scale). Descriptive statistics (frequency, percentage, mean, SD, etc.) were used to describe study participants and variables. Inferential statistics were used to analyze the relationships, associations, and correlations between resilience and relapse risk, the main variables, and the participants demographics. Result: Participants' mean total score for resilience was 72.92 out of a maximum possible score of 100 (SD = 16.99), while their mean total score for relapse risk was 59.07 out of a maximum possible score of 105 (SD = 12.23). Furthermore, examining the correlation between the resilience subscales and the relapse risk subscales revealed similar significant, negative, low-tomoderate correlations between all the subscales (r = -0.486). Discussion: Protective and risk factors to enhance resilience and reduce relapse risk in patients with SUD were discussed.